Printable G-putty for Frequency and Rate Independent, High Performance Strain Sensors - Coleman, Jonathan; Moebius, Matthias (My University, 2021)
While nanocomposite electromechanical sensors are expected to display reasonable conductivity and high sensitivity, little consideration is given to eliminating hysteresis and strain rate/frequency dependence from their response. For example, while G-putty, a composite of graphene and polysiloxane, has very high electromechanical sensitivity, its extreme viscoelasticity renders it completely unsuitable for real sensors due to hysteretic and rate-/frequency-dependent effects. Here it is shown that G-putty can be converted to an ink and printed into patterned thin films on elastic substrates. A partial graphene-polymer phase segregation during printing increases the thin-film conductivity by ×106 compared to bulk, while the mechanical effects of the substrate largely suppress hysteresis and completely remove strain rate and frequency dependence. This allows the fabrication of practical, high-gauge-factor, wearable sensors for pulse measurements as well as patterned sensors for low-signal vibration sensing.
PUBLISHED
Keywords: Percolation; Piezoresistance; Pressure sensing; Nanoscience & Materials; Nanotechnology; Physics